Microstructure evolution of cold sprayed copper coatings based on particle diameter control and its effect on corrosion resistance of aluminum-copper contacts - Wang, Yan; Tang, Qing; Wang, Ke; Xing, Ya-Zhe (Surfaces and interfaces, 2025)
Crevice corrosion of dissimilar metal contacts caused by potential difference severely hampers the technical application of the contacts. Coating technology applied to contact interfaces is an effective corrosion protection strategy, requiring a dense, well-bonded coating on the contact surface. In this study, cold-sprayed copper coatings were used to improve the corrosion resistance of aluminum-copper contacts. The evolution of the coating microstructure with particle size and its effect on the corrosion resistance of the contact were experimentally investigated. In order to understand the influence of particle size on the formation of the coating microstructure, a three-dimensional finite element computational model of the deposition behavior of copper particles was established based on the consideration of the effect of particle size on particle velocity. The experimental results show that the coatings produced with smaller particles not only have lower surface roughness and porosity, but also have improved coating-substrate and inter-particle bonding, and the coatings are more corrosion resistant and their protection to the contacts is improved. The simulation results show that the deformation and deposition rates of small particles are higher during the deposition process, and the interfacial temperature between small particles is higher than that of large particles at the end of deposition. This improves coating-substrate and inter-particle bonding, and thus reducing coating porosity. This study not only reveals the influence mechanism of copper particle size on the formation of the coating structure, but also proposes an effective method to improve the corrosion resistance of aluminum-copper contacts. [Display omitted]